Kombi's Online Ojek Survival Strategy in Facing Competition with Ojek Bases in Padangpanjang - Sefirel Maharani Putri; Endrizal; Emzia Fajri (Kirana Publisher (KNPub), 2024)
This study discusses the strategy used by kombi online motorcycle taxis in facing competition with base motorcycle taxis in Padangpanjang. The purpose of this study is to describe the background of people choosing base motorcycle taxis over combi online motorcycle taxis, as well as strategies carried out by kombi online motorcycle taxis to face the rampant competition of base motorcycle taxis in Padangpanjang. The research method used is qualitative research. Data collection techniques include field observations, interviews, and documentation. The theory used is Talcott Person's theory of Functionalism of Adaptation, Goal Attainment, Integration, and Latency (AGIL) Structures. The findings in this study explain that kombi online motorcycle taxis have several strategies to survive in the face of the rise of base motorcycle taxis in Padangpanjang. The strategies used by kombi online motorcycle taxis such as providing convenience in terms of access, security services, affordable prices, and socializing this kombi online motorcycle taxi to the people of Padangpanjang, as well as how to adapt amid the habits of the people of Padangpanjang who often use base motorcycle taxis and the presence of kombi as an online transportation service Those in Padangpanjang City certainly have certain goals in order to survive and be accepted by the people of Padangpanjang